Evaluating ten years of ‘strategizing’ for poverty reduction : A cross-sectional appraisal of the Poverty Reduction Strategy Paper (PRSP) initiative /: A cross-sectional appraisal of the Poverty Reduction Strategy Paper (PRSP) initiative. (March 2011) - (Doctoral student in economics), Marshall, Richard; Walters, Bernard
No abstract available